The Adaptation Of A Machine-Learned Sentence Realization System To French - Smets, Martine; Gamon, Michael; Corston-Oliver, Simon; Ringger, Eric (Association for Computational Linguistics, 2003)
We describe the adaptation to French of a machine-learned sentence realization system called Amalgam that was originally developed to be as language independent as possible and was first implemented for German. We discuss the development of the French implementation with particular attention to the degree to which the original system could be re-used, and we present the results of a human evaluation of the quality of sentence realization using the new French system.